GONE HOME: o Gótico Literário na trama do videogame. - MELO, Ludmila Gratz (2019)
This article aims to analyze the game Gone home in the light of the gothic genre and the studies about intertextuality and dialogism. This research aims to observe how literary texts manifest themselves in a typical media of the 21st century, such as the video game, and it also aims to point out the possibilities offered by the newer media. The video game Gone Home – created by The Fullbright Company in 2013 – seems to be, at least at first, a horror story, but the game proves itself to be part of the Gothic tradition, a type of fiction that often represents otherness and the repressed elements of culture by means of its conventions – which include representations of the supernatural, images of insanity and houses with hidden secrets. In addition to sharing aspects with other gothic works, the game also references specific texts of the genre, such as novels, tv shows, and movies. Therefore, we chose to analyze the presence of gothic texts and utterances in the game. For this purpose, we used theorists from the field of literary criticism – particularly those with studies about Dialogism and Intertextuality, in order to justify the not always obvious existence of literary texts and utterances with more than two hundred years of existence in a videogame produced in the 21st century, such as Mikhail Bakhtin (1981, 1992, 1997, 1998), José Luiz Fiorin (2008), Roland Barthes (1987, 2001, 2004) and Julia Kristeva (1974). We also used academics from the field of Gothic Fiction, such as Ellen Moers (1976), Andrew Smith (2007) and Jerrold E. Hogle (2002), to better understand the Gothic conventions used by the game and by the works of the Literary Gothic that will be presented here. Our findings confirm the presence of Gothic Fiction in the plot, as well as allusions to texts of the Literary Gothic, as it can be seen in more detail in the analysis.